Readiness of health facilities to manage individuals infected with COVID-19, Uganda, June 2021 - Mwine, Patience 1*,1, 1, 1; Ahirirwe, Sherry R.; Nansikombi, Hilda T.; Senyange, Shaban; Monje, Fred; Kyamwine, Irene B.; Ario, Alex R.; Harris, Julie R. (BMC Health Services Research, 2023)
The COVID-19 pandemic overwhelmed the capacity of health facilities globally, emphasizing the need for readiness to respond to rapid increases in cases. The first wave of COVID-19 in Uganda peaked in late 2020 and demonstrated challenges with facility readiness to manage cases. The second wave began in May 2021. In June 2021, we assessed the readiness of health facilities in Uganda to manage the second wave of COVID-19.